Diagnosis of hemostatic disorders in patient with sepsis caused by a triple infection of M. tuberculosis, P. aeruginosa, Kl. pneumoniae - M. V. Chirtsova; A. A. Khvorostov; N. V. Tursunova (Туберкулез и болезни лёгких)
The article describes a clinical case of successful treatment of the patient (37 years old) with focal tuberculosis of the single left lung in the consolidation phase, empyema of the right pleural cavity, who developed multiple organ failure syndrome, hypercoagulation and sepsis, caused by a triple coinfection with M. tuberculosis, P. aeruginosa, and Kl. pneumoniae.